2014
DOI: 10.14233/ajchem.2014.18198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Macromolecule Absorbent Resins on the Moisture Characteristics of Major Soil Type on Loess Plateau

Abstract: Macromolecule absorbent resins have an incredibly strong water absorbing capacity and can absorb moisture content several hundred or even thousand times higher than that of its own. More than 85 % of the absorbed moisture may be used by crops. Due to the cross linkage of molecular structure, the moisture absorbed by the molecular network cannot be extracted using general physical methods, thus contributing to the strength of the water retentivity. Due to its unique structure and excellent performance, PAM (pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…WRAs are soil amendments that can promote plant growth by improving soil structure, aggregation, and water availability [27][28][29]. The incorporating of WRAs into the soil can enhance its permeability, porosity, and water-retention capacity, hence improving soil conditions that facilitate plant growth [13,29]. The results of the principal component analysis revealed that most of fruit quality indexes were associated with the addition of WRAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…WRAs are soil amendments that can promote plant growth by improving soil structure, aggregation, and water availability [27][28][29]. The incorporating of WRAs into the soil can enhance its permeability, porosity, and water-retention capacity, hence improving soil conditions that facilitate plant growth [13,29]. The results of the principal component analysis revealed that most of fruit quality indexes were associated with the addition of WRAs.…”
Section: Discussionmentioning
confidence: 99%
“…Water-retaining agents (WRAs) are high-molecular cross-linked polymers that can improve the water-holding capacity of the soil [11,12]. When mixed with soil, WRAs can improve its physical properties by reducing soil bulk density and increasing soil aggregation, permeability, porosity, and water-retention capacity [11,13]. WRAs are soil improvers that can decrease soil strength and aggregate stability, which can enhance soil and water conservation and encourage plant development [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the water supply capacity of soils, superabsorbent resins have been introduced [ 16 ]. Its special three-dimensional-like molecular chain structure allows it to absorb and conserve large amounts of water in a short time [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its special three-dimensional-like molecular chain structure allows it to absorb and conserve large amounts of water in a short time [ 17 ]. Once the water content of the soil is low, the water stored in the resin is gradually released by the suction of the substrate and supplied to the plant growth, thus alleviating the drought stress [ 16 ]. Studies have shown that, on the one hand, the resin improves soil fertility by increasing the ability to retain water and hold nutrients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%